Bis[μ-bis-(diphenyl-phosphino)methane-κP:P']bis-[(chloro-difluoro-acetato-κO)silver(I)](Ag-Ag). - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, [Ag(2)(C(2)ClF(2)O(2))(2)(C(25)H(22)P(2))(2)], consists of two half-mol-ecules, each Ag(I) ion lying on a center of symmetry. In each complete mol-ecule, two bis-(diphenyl-phosphino)methane ligands bridge two Ag(I) ions, which are further coordinated by one chloro-difluoro-acetate ligand, giving T-shaped geometries and short intra-molecular Ag⋯Ag distances of 3.1078 (6) and 2.9950 (6) Å. In one mol-ecule, the unique -CF(2)Cl group is rotationally disordered over two sites with approximate occupancies of 0.53 and 0.47 for the major and minor components, respectively.